Sekolah Ramah Anak Pada Peserta Didik Penyandang Disabilitas Tunagrahita (Studi Kasus Sekolah Luar Biasa Melati Aisyiah Kabupaten Deli Serdang) - Arpani, Putri; El Muhtaj, Majda (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2023)
AbstractChild-friendly school (CFS) is a concept, program, and model that places children as a key educational subject whose rights are protected and respected in the whole of the learning and policy-making process in schools. SRA aims to ensure children enjoy their rights at school safely and healthily. This paper examines the essence of SRA and its contribution to respecting and protecting the rights of children with mental disabilities, in particular, intellectual disability at the Melati Aisyiah Special School (SLB) in Deli Serdang Regency. This article uses a case study approach to explain the general and special conditions that occur. Data collection through interviews was carried out to support library data from various reading sources, such as books, journals and other relevant reading sources. This article also finds that SRA is the appropriate concept to be implemented because fulfilling children's rights, especially for vulnerable groups with intellectual disabilities as children with special needs, requires a commitment and good actualization space supported by stakeholders to ensure the availability of a healthy and safe school environment.————AbstrakSekolah Ramah Anak (SRA) merupakan konsep dan model yang menempatkan anak sebagai subjek pendidikan yang dilindungi dan dihormati hak-haknya dalam setiap proses pembelajaran dan pengambilan kebijakan di sekolah. SRA bertujuan memastikan anak-anak menikmati hak-hak mereka di sekolah dengan aman dan sehat. Tulisan ini mengkaji esensi SRA dan kontribusinya dalam upaya menghormati dan melindungi hak-hak anak penyandang disabilitas grahita di Sekolah Luar Biasa (SLB) Melati Aisyah di Kabupaten Deli Serdang. Artikel ini menggunakan pendekatan studi kasus untuk menjelaskan kondisi umum dan khusus yang terjadi. Koleksi data melalui wawancara dilakukan untuk mendukung data kepustakaan dari berbagai sumber bacaan, seperti buku, jurnal dan sumber bacaan lain yang relevan. Artikel ini menemukan bahwa SRA adalah konsep yang tepat untuk dilaksanakan karena pemenuhan hak-hak anak, khususnya kelompok rentan penyandang disabilitas grahita sebagai anak berkebutuhan khusus membutuhkan ruang aktualisasi yang baik yang didukung ketersediaan lingkungan sekolah yang sehat dan aman.